Philosophy, mysticism, and the political : essays on Dante - Cacciari, Massimo; Carrera, Alessandro, 1954-; Mobili, Gigio (Albany : State University of New York Press, 2021)
Nine masterful essays on Dante's Divine Comedy and his political theology by one of today's leading Italian philosophers.
Includes bibliographical references and index.
Online resource; title from PDF title page (ProQuest Ebook Central platform, viewed June 7, 2022).
JSTOR
Keywords: Dante Alighieri, -- 1265-1321.; Dante Alighieri, -- 1265-1321 -- Political and social views; Cacciari, Massimo -- Translations into English; Cacciari, Massimo; Dante Alighieri, -- 1265-1321; Divina commedia (Dante Alighieri); Political and social views; Translations; Literary criticism; Essays; Essays; Literary criticism; Critiques littéraires.